SCREENING AND EVALUATION OF SECONDARY METABOLITES PRESENT IN PIPER CUBEBA - NIRMALA NITHYA R,; SAI NANDHINI R, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Bioactive compounds like phytochemicals are extracted mainly from plants, as they serve as traditional herbal medicine. The secondary metabolite such as alkaloids, flavonoids, and phenolic compounds serve as natural antioxidants and has been widely used due to its therapeutic applications. The objective of this study was to do preliminary phytochemical screening of the spice Piper cubeba. Methods: Totally, three solvents were used to prepare the extract. Of all the three extracts used, methanolic extract showed higher release of secondary metabolites when compared to ethyl acetate and hexane extract. Further quantitative analysis was carried out with the methanolic extract. Results: The presence of alkaloids, flavonoids, phenolic compounds, and tannins was observed. A significant result such as 1040 μg of Gallic acid equivalent/g of total concentration of flavonoid and 1280 μg of quercetin equivalent/g of total phenolic content was obtained.